2018
DOI: 10.1093/jisesa/iey123
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Method to Evaluate the Reproductive Potential of Phymastichus coffea (Hymenoptera: Eulophidae) in Hypothenemus hampei (Coleoptera: Curculionidae: Scolytinae) Under Laboratory Conditions

Abstract: Life fertility tables were constructed for Phymastichus coffea LaSalle, the only known endoparasitoid wasp that attacks the adult female of the coffee berry borer (CBB) Hypothenemus hampei Ferrari. No preoviposition period was observed, and the parasitoid female attacked the CBB females immediately after emergence. The reproductive period was 20.33 (±0.87 SE) h and the postreproductive period of 14.78 (±0.99 SE) h. Mean generation time was 37 d. Median longevity for female and male fed on honey-water solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Parasitoids were held for mating and oocyte maturation and provided with 50% (w/v) honey (raw organic) solution for ~ 2 h before being used in the experiments (López-Vaamonde and Moore 1998). Infante et al (1994) reported that P. coffea does not go through a preoviposition period and exhibits facultative arrhenotokous-type parthenogenesis, where the female parasitizes its host before or after copulation, producing haploid males (Portilla and Grodowitz 2018). Feldhege (1992) reported a preoviposition period of between 5 min and 4 h. The adult parasitoids are very short-lived: males (~ 8-48 h) and females (~ 16-72 h) (Vergara et al 2001;Rojas et al 2006;Espinoza et al 2009;Portilla and Grodowitz 2018).…”
Section: Parasitoid Phymastichus Coffeamentioning
confidence: 99%
See 2 more Smart Citations
“…Parasitoids were held for mating and oocyte maturation and provided with 50% (w/v) honey (raw organic) solution for ~ 2 h before being used in the experiments (López-Vaamonde and Moore 1998). Infante et al (1994) reported that P. coffea does not go through a preoviposition period and exhibits facultative arrhenotokous-type parthenogenesis, where the female parasitizes its host before or after copulation, producing haploid males (Portilla and Grodowitz 2018). Feldhege (1992) reported a preoviposition period of between 5 min and 4 h. The adult parasitoids are very short-lived: males (~ 8-48 h) and females (~ 16-72 h) (Vergara et al 2001;Rojas et al 2006;Espinoza et al 2009;Portilla and Grodowitz 2018).…”
Section: Parasitoid Phymastichus Coffeamentioning
confidence: 99%
“…Sanitation and biological control (using parasitoids, predators and entomopathogenic microorganisms) are the most sustainable, environmentally friendly and widely used non-chemical control methods. The parasitoids, Cepahlonomia stephanoderis Betrem, C. hyalinipennis Ashmead and Prorops nasuta Waterston (Hymenoptera:Bethylidae), Heterospilus coffeicola Schneideknecht (Hymenoptera:Braconidae) and Phymastichus coffea LaSalle (Hymenoptera:Eulophidae), all of African origin, have been introduced in many coffee producing countries, particularly in Central and South America (Klein-Koch et al 1988;Barrera et al 1990;Baker 1999;Jaramillo et al 2005;Portilla and Grodowitz 2018), but none have been released in Hawaii. In Hawaii, the primary methods for controlling H. hampei are sanitation (frequent harvests and removal of all left over coffee berries after harvest) and applications of the biopesticide Beauveria bassiana (Ascomicota:Hypocreales), an entomopathogenic fungus (Aristizábal et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How these phenotypes arise mechanistically remains unknown; however, the dominant hypotheses include effector-driven initiation and maintenance of galls [12, 34, 35] and hormone induced tissue differentiation [36]. Comparative analyses among congeneric gallers [37] correlates genes encoding secretory proteins to their life history, but additional examinations are required to understand the evolutionary origin, significance, and functions of these types of proteins in search of evidence in support of existing hypotheses. To this end, we combined transcriptome and genome sequencing with protein interaction assays to characterize a discrete clade of genes with effector-like attributes in the cosmopolitan and agriculturally significant galling herbivore, Daktulosphaira vitifoliae .…”
Section: Introductionmentioning
confidence: 99%
“…Current review in this topic reports some successful systems, both traditional and modern, for artificially rearing different insects in various parts of the world, using synthetic nutrients and substrates. These allow mass production of parasites like Hypothenemus hampei ( Portilla et al 2006 , 2018 ), Sitrotroga cerealella ( Palma et al 2011 ), and Anastrepha fraterculus ( Flores et al 2012 ), including some biocontrol agents like Ladybird Coleomegilla maculata ( Riddick and Zhixin 2015 ), at various stages without the need for a plant host; however, no reports have been found related to unnatural or artificial systems for breeding cochineal insects that do not use their common and natural host ( Opuntia sp ).…”
mentioning
confidence: 99%